2016
DOI: 10.3390/nu8100666
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Intakes, Physical Activity, and Calcaneus BMC among School-Going 13-Year Old Malaysian Adolescents

Abstract: Background: Dietary calcium and vitamin D are essential for bone development. Apart from diet, physical activity may potentially improve and sustain bone health. Objective: To investigate the relationship between the dietary intake of calcium and vitamin D, physical activity, and bone mineral content (BMC) in 13-year-old Malaysian adolescents. Design: Cross-sectional. Setting: Selected public secondary schools from the central and northern regions of Peninsular Malaysia. Participants: The subjects were from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…For vitamin D, 1.37 μg/day intake was not within the normal range for the recommended intake of Malaysian population and is far from RNI 2017. The results of the previous study among postmenopausal women, pregnant women as well as adolescent were in accordance with the present study with the majority of respondents fail to meet the RNI of Malaysia for dietary vitamin D (Rahman et al, 2004;Zaleha et al, 2015;Suriawati et al, 2016). Therefore, interventions and stricter reinforcements of existing guidelines for vitamin D supplementation are needed in Malaysia, especially for groups at risk of vitamin D insufficiency or deficiency.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For vitamin D, 1.37 μg/day intake was not within the normal range for the recommended intake of Malaysian population and is far from RNI 2017. The results of the previous study among postmenopausal women, pregnant women as well as adolescent were in accordance with the present study with the majority of respondents fail to meet the RNI of Malaysia for dietary vitamin D (Rahman et al, 2004;Zaleha et al, 2015;Suriawati et al, 2016). Therefore, interventions and stricter reinforcements of existing guidelines for vitamin D supplementation are needed in Malaysia, especially for groups at risk of vitamin D insufficiency or deficiency.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies found that the calcium intake of Malaysians averaged between 357 mg/day to 397.2 mg/ day (Mirnalini et al, 2008;Zainuddin, 2015;Suriawati et al, 2016). Hence, 348.3 mg/day (34.8% RNI 2017) calcium intake by respondents in the present study was close to the average Malaysian adults' intake, which is consistently below the RNI.…”
Section: Discussionsupporting
confidence: 61%
“…The results of another two cross-sectional studies in Spanish revealed that high Ca intake associated with a higher BMD in children between 5 and 12 years old (12), and total BMD was positively related to Ca intakes in adolescents aged 12.5 to 17.5 years (13), respectively. However, some other studies supported that Ca intake had no effect on BMD (14,15,16,17,18). A previous review by Lanou et al (6) reported that nine cross-sectional studies of 13 did not find an association of dietary Ca intake with BMD or bone mineral content in adolescent girls.…”
Section: Discussionmentioning
confidence: 99%
“…In the present cross-sectional study, we found dietary Ca intake positively correlated with total BMD. In addition, the strongest association was observed in 12-15 year old whites, 8-11 year old and 16-19 year old Mexican Americans, and [16][17][18][19] year old individuals from other races, in whom each quintile of Ca intake was increased. The trend tests remained significant in all groups except the 8-11 year old other race group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation